PENGUATAN LITERASI KEAGAMAAN MELALUI VIDEO INTERAKTIF DAN KUIS BAGI SISWA SEKOLAH DASAR - Yulia, Sispa; Johar, Rama Dhini Permasari; Erwan; Ediz, M Hidayat; Febria, Thomas; Zulfadli (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
This community service activity was motivated by the low level of religious literacy in grade 4 of SDN 13 Bukit Tandang, as seen from the results of direct observation and pre-tests conducted by the author. The purpose of this community service activity is to improve the religious literacy skills of grade 4 students at SDN 13 Bukit Tandang. The method used by the author is Service Learning (SL). The data collection techniques used by the author consist of observation, questionnaires, and direct interviews. Based on the results of the community service that the author has done, it was found that learning religious literacy in grade 4 students of SDN 13 Bukit Tandang through interactive videos and quizzes showed a significant increase compared to traditional learning methods. Based on the results of the post-test that the author did, the majority of students' scores increased by 50% in the good category. when compared to those who got the good category in the pre-test, namely 20%. The application of interactive video media and quizzes has proven effective in improving the understanding and religious literacy skills of grade 4 students of SDN 13 Bukit Tandang.